2024
DOI: 10.1007/s10840-023-01728-0
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial posterior wall isolation using pulsed-field ablation: procedural characteristics, safety, and mid-term outcomes

Patrick Badertscher,
Diego Mannhart,
Simon Weidlich
et al.

Abstract: Background Non-pulmonary vein (PV) ablation targets such as posterior wall isolation (PWI) have been tested in patients with persistent atrial fibrillation (AF). Pulsed-field ablation (PFA) offers a novel ablation technology possibly able to overcome the obstacles of incomplete PWI and concerns of damage to adjacent structures compared to thermal energy sources. Our aim was to assess procedural characteristics, safety, and mid-term outcomes of patients undergoing PWI using PFA in a clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…10,11,27 Recent studies also confirmed the safety and feasibility of PFA PVI + PWA. 15,16,18,19 A meta-analysis of posterior wall isolation via RF revealed 15 major complications, including 2 atrioesophageal fistulas, while none of the patients in this study experienced any esophageal complications even after extensive ablation. 28 Importantly, none of the patients in this study had adverse events that could be attributed to prolonged ablation time, especially with a median LAPW PFA time of 8 min.…”
Section: Safety Outcomesmentioning
confidence: 64%
See 1 more Smart Citation
“…10,11,27 Recent studies also confirmed the safety and feasibility of PFA PVI + PWA. 15,16,18,19 A meta-analysis of posterior wall isolation via RF revealed 15 major complications, including 2 atrioesophageal fistulas, while none of the patients in this study experienced any esophageal complications even after extensive ablation. 28 Importantly, none of the patients in this study had adverse events that could be attributed to prolonged ablation time, especially with a median LAPW PFA time of 8 min.…”
Section: Safety Outcomesmentioning
confidence: 64%
“…15,16 The latest meta-analysis comparing PVI with PVI + LAPW ablation in PerAF patients reported higher rates of arrhythmia freedom and reduced recurrence of overall atrial tachyarrhythmia in the PVI + LAPW group, even thoughGunawardene et al and Turagam et al …”
mentioning
confidence: 99%
“…The feasibility, rapidity, durability, and safety of the multispline PFA catheter alone (flat "flower" configuration rather than focal catheter) among PeAF patients (n = 25) for ICE-guided PVI+LAPWI were demonstrated by Reddy et al in a preliminary small-sized study (PersAFOne). 14 Badertscher et al 18 showed that PFA-based PVI plus LAPWI (indication and endpoint based on 3D-EAM) was achieved in 100 patients (76% PeAF) at a median of 66 min and 16 (12-20) PFA lesions without any major complication and a 15% recurrence rate at 144 (94-279) days follow-up. They performed two anchor lesions per vein extending to LAPW, then the wire was pulled back and the PFA catheter was rotated along the entire LAPW in a flower configuration in an overlapping fashion which revealed a 95% first-pass isolation rate.…”
mentioning
confidence: 99%